Identification Of Mountain Bike Sports Talent In Children Aged 10-15 Years Based On R Programming Software (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
MTB has strategic potential in the context of global and local sports development. Internationally, this discipline is one of the most popular events in the Olympics and world championships. In Indonesia itself, MTB is growing rapidly as both a recreational and competitive sport, with an increasing number of communities and events being held. This potential opens up great opportunities to produce accomplished athletes if training is directed appropriately from an early age. Therefore, accurate talent identification methods are needed to ensure that a high interest in MTB can be converted into real achievements in the future. This study aims to identify mountain biking talent in children aged 10-15 years using R programming software. Based on the results of the study, it was found that 13 respondents (10.83%) had talent in mountain biking. Meanwhile, the remaining 107 respondents (89.13%) did not have talent in mountain biking. The results of this study conclude that the application of technology and statistical methods through R Programming contributes positively to identifying athletic talent at the elementary school level. This study only focuses on identifying talent. For future research, it is hoped that this study can be developed specifically in the anthropometric aspects related to badminton talent.